The use of Round Robin technique to improve students' speaking skill - Rosnani Sahardin; Hendra Heriansyah; Mutia Dara Authari (Universitas Syiah Kuala, 2019)
This study aims to find out whether the use of Round Robin Technique can improve the speaking skill of junior high school students. This research was conducted in one class and applied the pre-experimental design that was one group pre-test and post-test design. There were four meetings in this research including pre-test and post-tests. The sample is students in one class that consisted of 32 students, with 15 females and 17 males. The instruments used to obtain the data were pre-test and post-test. The mean of the student speaking score of the pre-test was 43.71 and the mean of the post-test was 79.2. The improvement from pre-test to the post-test was 35.49 points. The average score of the students was 79.2, it was higher than the Criteria Mastery of Learning (or KKM, Kriteria Ketuntasan Minimal) of a junior high school in Banda Aceh, which is 70.00. The result of this study can be shown in the t-test that there was an improvement of students’ speaking skill, with the t-test of 25.3, the degree of freedom is 31 and t-table is 1.696. Based on the result of the test, it can be concluded that the use of Round Robin Technique improved the students’ speaking skills. This technique offered the students’ chances to share ideas and opinion with their peers, speak up and express their argument in class.